TUGAS DAN FUNGSI BADAN PERMUSYAWARATAN DESA TERHADAP PENGAWASAN KINERJA KEPALA DESA SESUAI DENGAN UNDANG-UNDANG NOMOR 6 TAHUN 2014 TENTANG DESA: (Studi di Desa Sarirejo Kec. Balen Kab. Bojonegoro) - Sholihuddin (Program Studi Hukum Tata Negara dan diterbitkan oleh Program Studi Hukum Tata Negara dan Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Sunan Drajat Lamongan, 2023)
BPD is an institution that has the power to approve village regulations which will serve as guidelines for implementing village development. BPD also has the power to convey the aspirations of citizens. Submitting aspirations is carried out through several work stages, namely the BPD must explore community aspirations, accommodate community aspirations submitted to the BPD and manage community aspirations as positive energy in formulating village policy steps. The type of research taken in this proposal is sociological juridical research. The location of this research is in Sarirejo Village, Balen District, Bojonegoro Regency. Where in Sarirejo Village. Data obtained primary or secondary, for quantitative analysis, is then presented descriptively, namely by explaining, describing and illustrating problems and their solutions which are closely related to the researcher's discussion. The results of this research are that the function in making regulations is more implemented and realized, in contrast to the function in accommodating community aspirations and supervising the performance of the Village Head which has not been optimal in its implementation due to a lack of understanding by BPD members of their duties and functions based on applicable regulations.